Clays and Clay Minerals, Vol. 60, No. 4, 420–439, 2012. - Cheshire, Michael C.; Bish, David L.; Brassell, Simon C. (The Clay Minerals Society, 2012)
Most previous studies of the kaolin deposits in the southeastern United States have focused on their mineralogy and petrology to understand better the depositional and diagenetic environments of the kaolins. Many studies suggest, however, that much of the information held within the minerals was changed during extensive post-depositional groundwater and microbial alteration. Organic d13C and biomarker analyses were used, therefore, to provide further information on the nature of the original sediments, the depositional environment(s), and the amount of diagenetic alteration that has occurred in Georgia kaolin deposits. Two different types of kaolin can be discerned, based on their total organic carbon contents: organic-lean kaolin and lignitic kaolin. The bulk organic d13C in the Georgia kaolins ranges from ~-26 to -19% (VPDB, Vienna Pee Dee Belemnite standard), with a noticeable enrichment in 13C with decrease in organic carbon concentration. The lean kaolins are by far the more dominant types, with an organic-matter composition primarily of C16-C22 n-alkanes, C16 and C18 fatty acids, and unresolved complex mixtures. Lignitic kaolin has a distinctly different organic matter (OM) composition. The lignitic material is primarily C15-C33 n-alkanes with a greater abundance of C23-C31 n-alkanes and lesser amounts of resinous and microbial constituents along with the oxidized forms of the saturated lipid fractions. Biomarker data suggest that the lignitic material is primarily terrestrially derived from conifers with minor input from microbial lipids. The OM in both types of kaolin shows strong signs of microbial decomposition that yield the organically lean kaolins. The oxidation of the detrital organic matter would subsequently yield organic acids that would have exerted significant influence on the mineralogy and metal mobility.
Organic Geochemical Composition Of The Georgia Kaolins: Insights Into Formation And Diagenetic Conditions
gsccm60408-che.pdf -- 2,726KB
Keywords: Periodicals; Geology; Biomarkers; Diagenesis; Geochemistry; Georgia; Hopanoids; Isotopes; Kaolinite; Lignite; Microorganisms; Organic Acids